Świątynie Wenus Erycyńskiej w starożytnym Rzymie - Franczak Leeds, Aneta (In Gremium. Studies in History, Culture and Politics, 2009)
The temples of Venus Erydna in ancient Rome During the Second Punic War, the Romans brought from Sicili cult of a goddess identified with Venera and called her Venus Erycina. The first temple dedicated to ber was built in the City center on the Capitoline Hill in 215 B.C. The second one was built in 181 B.C. this time, however, outside the religious boundary of the City, extra portam Collinam.